2002
DOI: 10.1051/agro:2002065
|View full text |Cite
|
Sign up to set email alerts
|

Management of nitrogen fertilization of winter wheat and potato crops using the chlorophyll meter for crop nitrogen status assessment

Abstract: This paper presents experimental results from a new field-scale N management strategy for winter wheat and potato crops in Belgium. At the beginning of the season, a global N recommendation is given using the balance-sheet method. The crop development and related N needs are strongly influenced by unexpected factors during the growing season. Therefore, the N predictive recommendation needs to be adapted to the crop N status. For this assessment, the chlorophyll meter was preferred over several plant diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 3 publications
1
28
1
2
Order By: Relevance
“…Crop N status could reliably be measured at ZGS 32 in this study. Previous studies have also found leaf chlorophyll index measured using a SPAD-502 meter to be effective in assessing crop N status for wheat at late tillering and at more mature growth stages (Follett and Follett 1992;Fox et al 1994;Peltonen et al 1995;Denuit et al 2002). However, fertilizer N applied at ZGS 32 in this study primarily influenced grain protein, and was of limited value in optimizing grain yield.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Crop N status could reliably be measured at ZGS 32 in this study. Previous studies have also found leaf chlorophyll index measured using a SPAD-502 meter to be effective in assessing crop N status for wheat at late tillering and at more mature growth stages (Follett and Follett 1992;Fox et al 1994;Peltonen et al 1995;Denuit et al 2002). However, fertilizer N applied at ZGS 32 in this study primarily influenced grain protein, and was of limited value in optimizing grain yield.…”
Section: Resultsmentioning
confidence: 71%
“…Such a system includes application of some fertilizer N in spring, followed by additional fertilizer applied later in the growing season as required based on crop N status (Denuit et al 2002). Leaf chlorophyll index, as measured using a SPAD-502 meter, has been found to be effective in measuring wheat N status (Fox et al 1994;Peltonen et al 1995).…”
Section: Mots Clésmentioning
confidence: 99%
“…Use of SPAD measurements to guide in-season fertilizer N management was demonstrated to reduce N losses without loss of corn yield . SPAD meter readings are sensitive to the leaf chosen and the measurement location on the leaf (Hoel 1998) and therefore well-defined sampling protocols are required (Denuit et al 2002). Disadvantages of the SPAD meter include the need for cultivar specific critical values (Minotti et al 1994) and the requirement for considerable manual leaf sampling in order to produce reliable average values.…”
Section: Plant-based Diagnostic Testsmentioning
confidence: 99%
“…Additional applications of fertilizer N are made during the growing season based on crop monitoring results, usually using an optical measurement of crop N status. Such decision support systems have been developed for potatoes and wheat using the SPAD-502 meter (Denuit et al 2002;Olivier et al 2006) and for wheat using basal stem tissue sap nitrate concentration (Justes et al 1997).…”
Section: Decision Support Systemsmentioning
confidence: 99%
“…Photosynthetic proteins account for more than half of the N in a crop leaf, and crop foliar Chl content is significantly correlated with foliar N content (Evans, 1989). Therefore, the SPAD-502 chlorophyll meter (SPAD) reading should reflect foliar N status (Denuit et al, 2002;Le Bail et al, 2005). The relationship between SPAD readings and foliar Chl or N for other crops has been intensively studied and is known to be affected by plant variety (Hoel, 2002), growing conditions (Campbell et al, 1990), sampling point (Chapman and Barreto, 1997), leaf age (Jinwen et al, 2009), and other factors.…”
Section: Introductionmentioning
confidence: 99%